Molecular Cell Biology - Harvey, Lodish; Harvey, Lodish (New York : W H Freeman, 2007)
With its acclaimed author team, cutting-edge content, emphasis on medical relevance, and coverage based on landmark experiments, Molecular Cell Biology has justly earned an impeccable reputation as an authoritative and exciting text. The new Sixth Edition features two new coauthors, expanded coverage of immunology and development, and new media tools for students and instructors.
Includes bibliographical references; Index v.p.
Keywords: Cytology; Molecular biology; Environmental Biology